THE NEEDS FOR DEVELOPING TEACHERS IN SCHOOLS UNDER NONTHABURI CONSORTIUM 3 BASED ON THE CONCEPT OF CRITICAL THINKING DISPOSITION - Susilanurak, Pajaree; Petpon, Ponglikit (Journal of Educational Review Faculty of Education in MCU, 2024)
The purpose of this research is to study the needs of the development of teachers in schools under Nonthaburi consortium 3, based on the concept of critical thinking disposition. This study was conducted using a descriptive research approach. The population was 6 secondary schools under Nonthaburi consortium 3. The survey was completed by 247 people, who were all secondary school teachers in schools under Nonthaburi consortium 3. The tools used in the research were questionnaires on the current state and desired state of teacher development in schools under Nonthaburi consortium 3, based on the concept of critical thinking disposition. The data were analyzed by arithmetic mean, standard deviation, and the modified Priority Needs Index (PNIModified). The finding showed that the needs of the development of teachers in schools under Nonthaburi consortium 3, based on the concept of critical thinking disposition is at a high level (PNIModified = 0.322). When analyzing individual needs, it was found that systematicity were ranked the highest (PNIModified = 0.398), follow by critical thinking-confidence (PNIModified = 0.378), analyticity (PNIModified = 0.335), inquisitiveness (PNIModified = 0.311), and truth-seeking (PNIModified = 0.257). Meanwhile, open-mindedness had the least necessary needs index (PNIModified = 0.250)